Safety and immunogenicity following a homologous booster dose of CoronaVac in children and adolescents - Lei Wang; Zhiwei Wu; Zhifang Ying; Minjie Li; Yuansheng Hu; Qun Shu; Jing Li; Huixian Wang; Hengming Zhang; Wenbin Jiao; Lin Wang; Yuliang Zhao; et al. (Nature Communications, 2022)
Few countries have approved SARS-CoV-2 booster doses in children and adolescents due to insufficient evidence about the safety and interval vaccination. Here, the authors assess the safety and immunogenicity of a homologous booster dose of CoronaVac in a cohort of 3–17 year olds.